Analysis of the Development of Pencak Silat Interactive Learning Media - Rino Lusiyono Lucius; Zusyah Porja Daryanto; Suriani Sari; Ashadi Cahyadi (IKIP Budi Utomo Malang, 2023)
The objectives of this article are to check out the results of the development of the Pencak Silat Interactive Learning Media. This includes an analysis of the journal's core, results of research, and the effectiveness of developments undertaken to improve the quality of learning in Pencak Silat. The design of this analysis is a literature search using the PICOS approach, which is then analyzed using critical appraisal analysis to find similarities and differences between these journals. Based on a literature review of 10 journals, we conclude that the quality of his Pencak Silat learning in both primary and secondary school is improved through Pencak Silat Interactive Learning Media using various applications or software used for effective learning can be attached. Improved. to a higher university.